Financial Performance Analyisi Using Financiali Value Added, Refined Economic Value Added, and Cash Value Added in Banking Sub-Sector Companies on the Indonesia Stock Exchange for the 2019-2021 Period - Inri Marselina Lolo; Herman Karamoy; Djeini Maradesa (Indonesian Journal of Business Analytics, 2023)
Financial performance is an analysis that is used to determine the extent to which a company carries out its financial activities by using the rules of financial implementation properly and correctly. This study aims to analyze the financial performance of banking companies on the Indonesia Stock Exchange in the 2019-2021 period using financial value added (FVA), refined economic value added (REVA), and cash value added (CVA). This type of research used is descriptive research. The research was conducted on banking companies listed in the Infobank Stock Index15 on the Indonesia Stock Exchange. The data were obtained by using Documentation and Literature Study methods. The research results of the five banking companies that were examined showed that the FVA results tended to be positive (FVA > 0) because the FVA was negative (FVA < 0) only for BBRI companies in the 2019 period. REVA results tended to be negative (REVA < 0) because REVA was positive (REVA > 0) only for BBNI and BJBR companies in the two study periods. CVA results tend to fluctuate (CVA < 0) because negative CVA (CVA < 0) are only BBCA companies during the three-year study period.